IMPACT OF PHARMACEUTICAL BIOTECHNOLOGY - Aysha Aslam; Wajeeha Ishtiyaq (International Journal of Pharmacy & Integrated Health Sciences)
We are living in an era of transformation and miracles happen each day. Biotechnology is the combination of two words “technology and biology”. The domain of Biotechnology is very wide in which cells or cellular parts, biological pathways and organisms are used to develop new innovative technologies. Novel procedures, tools and products are developing day by day, which are used in research, agriculture, industry and the health care system. Pharmaceutical Biotechnology is the application of biotechnology principles and procedures in the development of drugs. Pharmaceutical biotechnology is the quite innovative, dynamic and rapidly emerging field and driving a global alteration from illness to wellness. Since last few years, pharmaceutical biotechnology has played a key role in drug research and development, and innovatory changes have been happening in health care setups, especially in field of oncology, infectious diseases and metabolic disorders. Due to the Pharmaceutical Biotechnology, a groundbreaking transformation is occurred in the field of drug discovery. Various biotechnology techniques (i.e. cell culture, genetic modeling and immunochemistry) use in drug discovery and have also paved the way to explore new avenues of drug discovery that are beneficial to the mankind.